Impact of Teachers’Attitudes on Students’ Academic Performance inPublic Secondary Schools in Ekiti State - Leonard, Shaibu (Innovations in Pedagogy and Technology, 2025)
The study examined the impact of teachers' attitudes on students' academic performance in public secondary schools in Ekiti State to explore the attitudes among public secondary school teachers specifically, the relationship between teachers' attitude and the academic performance of students, and factors influencing teachers' attitudes towards teaching in public secondary schools in Oye Local Government Area (LGA). Descriptive survey research was employed to describe the responses from a sample of 393 respondents selected using a stratified sampling technique. A validated instrument with an overall reliability index of 0.87, titled "Teachers' Attitude and Students' Academic Performance Questionnaire" (TASAPQ), was used for data collection to be exposed to data analysis by mean and standard deviation using a benchmark of 2.50 for decision-making and chi-square test of independence to test the hypotheses at an alpha level of 0.05. The analysis revealed that teachers have both positive and negative attitudes towards teaching; they are passionate and patient in the classroom, enthusiastic about their subject areas, and supportive of their students. The analysis also showed that teachers' teaching attitudes were significantly related to academic success among students in public secondary schools in Oye LGA. It further disclosed that factors affecting teachers' attitudes are the state of their remuneration, level of support from school administration, availability of teaching resources, level of teacher training and professional development, job satisfaction, teacher burnout, stress, and workload. The study suggested, among other things, that school management should encourage teachers to demonstrate positive attitudes towards teaching.